FEATURES OF THE LANGUAGE OF ARABIC NEWSPAPER - Aripova Zukhra (Journals Park Publishing, 2023)
The language of the press has a speech structure, which is manifested in the special selection of language tools and their activity. This article talks about the language features of Arabic newspaper texts in Arab countries and the problems of their translation into another language.
Keywords: press, article, Arabic language, newspaper texts, language, Arab countries.